Instagram Marketing Activities Of A Fast Fashion Brand In Response To Covid-19 Pandemic - et. al., Arina Nahya Nurnafia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is rooted from the phenomenon of the existence of social media as business platforms that many businesses adopt nowadays in order to communicate and interact with their customers. Social media marketing facilitates the sharing of information between consumers and organizations in social media. Instagram is a social media application that has been adopted widely by businesses, including by fashion brands. Yet, until recently there are limited knowledge and studies available about how fashion brands implement their marketing activities through social media during the Covid-19 pandemic, particularly on Instagram. Fast-fashion is one major segment of fashion industry currently. This research aims to explore how fast-fashion brands conduct their social media marketing strategies during the Covid-19 pandemic time and how they differ compared to before the pandemic. Thus, this research uses a single case study approach through a case of a global fast-fashion brand that conducts its activities and establish social media accounts in Indonesian market. The findings of this study show significant difference of social media marketing activities conducted by the brand on its Instagram brand community before the pandemic and during the pandemic that may give valuable insights for fashion businesses and theory development in social media marketing